Conformance of Malaysia e-commerce blogs with quality content theories - Hassan, Syahida; Zambri, Suzana; Kasiran, Mohd Khairudin; Mahli, Mohamad Tarmidi; Abd Ghani, Nor Farzana; Muhammad, Muziah (IBIMA Publishing, 2012)
Recently the use of blog as an e-commerce site has become popular in Malaysia.Significant changes can be seen in e-commerce usage as more people are connected to the Internet through faster broadband connection. Nonetheless, trust remains a major issue when it involves online transaction. Information displayed on the blog is vital and considered as one of the important factors to gain the consumer trust.This paper is a preliminary study particularly focusing on the conformance of Malaysia E-Commerce blogs with related theories on quality online content.Samples were taken from Malaysia e-commerce blogs to identify the information that is shared by the owner of respective blogs.The information collected from the blog is then compared to the quality contents’ theories.Descriptive statistic is used to describe the findings. Findings from this paper can be used as a guideline for entrepreneurs who intend to use blogs for e-commerce purposes.